A DIRECTIVE SPEECH ACT IN THE BLIND SIDE MOVIE BY JOHN LEE HANCOCK - Yosifya Nike Sarwoko; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
A speech act is an act performed by saying something. This study aims : 1) to find_out_thetypes of locutionary act, 2) to find out the types of perlocutionary act, and 3) to find out thetypes of illocutionary act in The Blind Side movie by John Lee Hancock. Moreover, this studyconcerned on the use of directive speech act. The researcher used qualitative method with thetype of a library research to describe and analyze the utterances that consisted of speech act.The method of collecting data is non-participant observation and documentation. Interactivemodel data of analysis used to analyze the data. The result of this study showed that : 1) therewere 227 utterances consisted of locutionary act which had no types, 2) there are 227utterances consisted of perlocutionary act which had no types and 3) there are 227 utterancesconsisted of illocutionary act which included asserives, declaratives, commisives, expressivesand declaratives. Furthermore, the writer found 131 utterances consisted of directive speechact which had 31 of requirements, 64 of questions, 20 of requestives, 6 of prohibitives, 3 ofpermissives and 7 of advisories. From the result of this research, the questions types inDirective Speech Act was the most dominant used by major and minor character as thespeakers.Keywords : Locutionary Acts, Perlocutionary Acts, Illocutionary Acts, DirectiveSpeech Act, A Qualitative Research